2010
DOI: 10.1061/(asce)gt.1943-5606.0000194
|View full text |Cite
|
Sign up to set email alerts
|

Face Stability Analysis of Circular Tunnels Driven by a Pressurized Shield

Abstract: Abstract:The aim of this paper is to determine the face collapse pressure of a circular tunnel driven by a pressurized shield. The analysis is performed in the framework of the kinematical approach of limit analysis theory. It is based on a translational three-dimensional multiblock failure mechanism. The present failure mechanism has a significant advantage with respect to the existing limit analysis mechanisms developed in the case of a frictional soil: it takes into account the entire circular tunnel face a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 296 publications
(87 citation statements)
references
References 17 publications
3
78
0
6
Order By: Relevance
“…More precisely, the present mechanism underestimates the critical collapse pressure by 10-20% with respect to the numerical model. The proposed mechanism is not the one leading to the most critical collapse pressure in the framework of the kinematical approach, as was demonstrated in Mollon et al (2010). Nevertheless, it was chosen for this study because its small computational cost makes possible the validation of CSRSM.…”
Section: Deterministic Modelmentioning
confidence: 99%
“…More precisely, the present mechanism underestimates the critical collapse pressure by 10-20% with respect to the numerical model. The proposed mechanism is not the one leading to the most critical collapse pressure in the framework of the kinematical approach, as was demonstrated in Mollon et al (2010). Nevertheless, it was chosen for this study because its small computational cost makes possible the validation of CSRSM.…”
Section: Deterministic Modelmentioning
confidence: 99%
“…Later, Leca and Dormieux (1990) proposed a 3D kinematically admissible mechanism for the upper bound analysis and obtained the upper bound solution for face stability in low-cohesion soil. The multi-block mechanism modeling for the slip surface in the collapses was introduced into upper bound analysis (Soubra 2000;Mollon et al, 2010). To study this problem in layered soils, Tang et al (2014) modified the kinematically admissible mechanism of Leca and Dormiuex (1990) for layered soils and investigated the influence of different soil layers on tunnel face stability.…”
Section: Introductionmentioning
confidence: 99%
“…To study this problem in layered soils, Tang et al (2014) modified the kinematically admissible mechanism of Leca and Dormiuex (1990) for layered soils and investigated the influence of different soil layers on tunnel face stability. Senent and Jimenez (2015) improved the mechanism of Mollon et al (2010) to investigate the possibility of partial collapse in layered soils. The rational mechanism for the problem of face collapse in frictional layered soils was also discussed well in Ibrahim et al (2015)'s research.…”
Section: Introductionmentioning
confidence: 99%
“…Huang (2013) and Fraldi (2011) concluded that collapse is the main failure mode in tunnels at a specific depth [12,13]. Mollon (2010) and Wonga (2012) conducted an analysis of the passive failure mechanism of tunnel faces [14,15]. Corkum (2007) and Chang (2007) determined that the failure mechanism of rocks around deep buried tunnels [16,17].…”
Section: Introductionmentioning
confidence: 99%